Methotrexate-Induced Pancytopenia and Mucositis Caused by Medication Error - Amissah-Arthur, Maame-Boatemaa (Ghana Med J, 2020)
The use of methotrexate in routine clinical practice is becoming more common among specialties such as rheumatology, dermatology, oncology and obstetrics. General clinicians are increasingly encountering patients on this drug. Though it has a high safety profile, there is a recognised risk of acute toxicity or long-term complications associated with its use, which can be worsened by several factors such as advanced age, moderate to severe renal impairment, low folate level and/or inadequate folate supplementation, hypoalbuminaemia, polypharmacy causing drug-drug interactions and wrongful administration. We present a case of a 45-year old woman with rheumatoid arthritis who presented with acute pancytopaenia and mucositis due to methotrexate toxicity. We highlight its peculiar dosing regimen to minimise prescribing errors. FUNDING: None